Exploring the association between BDNF related signaling pathways and depression: A literature review - Yuchen Fan; Xinchi Luan; Xuezhe Wang; Hongchi Li; Hongjiao Zhao; Sheng Li; Xiaoxuan Li; Zhenkang Qiu (Brain Research Bulletin)
Depression is a debilitating mental disease that inflicts significant harm upon individuals and society, yet effective treatment options remain elusive. At present, the pathogenesis of multiple depression is not fully clear, but its occurrence can be related to biological or environmental pathways, among which Brain-derived neurotrophic factor (BDNF) can unequivocally act on two downstream receptors, tyrosine kinase receptor (TrkB) and the p75 neurotrophin receptor (p75NTR), then affect the related signal pathways, affecting the occurrence and development of depression. Accumulating studies have revealed that BDNF-related pathways are critical in the pathophysiology of depression, and their interaction can further influence the efficacy of depression treatment. In this review, we mainly summarized the signaling pathways associated with BDNF and classified them according to different receptors and related molecules, providing promising insights and future directions in the treatment of depression.